The Science of Consumer Insights and Behaviour - Gurjar, Viraath (Journal of Advanced Research in Strategic Marketing Intelligence and Customer Engagement Optimization, 2025)
Understanding consumer behaviour is at the core of modern marketing strategies. By leveraging consumer insights, businesses can develop more effective marketing campaigns, product innovations, and customer engagement strategies. This review delves into the science behind consumer behaviour analysis, explores the methodologies used to gather consumer insights, and highlights the role these insights play in shaping successful marketing decisions. We explore both qualitative and quantitative approaches, including psychological theories, behavioural analytics, and the impact of cultural, social, and economic factors. Additionally, we examine the ethical considerations involved in the collection and usage of consumer data, ensuring privacy and transparency. Furthermore, the review highlights the significant influence of social media and influencers on consumer decisions, as well as emerging trends in predictive analytics and AI-driven consumer insights. The evolving landscape of consumer analytics is reshaping how businesses interact with their customers, providing new opportunities for personalized marketing, improved product offerings, and optimized customer journeys. The review also addresses the challenges businesses face in navigating the ethical implications of data usage, ensuring that consumer trust is maintained while driving long-term strategic growth.